2016
DOI: 10.21273/hortsci.51.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Polymorphic Expressed Sequence Tags-Simple Sequence Repeat Markers and Their Application in Analysis of Genetic Diversity of Chinese Bayberry (Morella rubra)

Abstract: Chinese bayberry (Morella rubra) is an economically important subtropical evergreen fruit crop native to China and other Asian countries. For facilitating cultivar discrimination and genetic diversity analysis, a total of 38 high-quality and highly polymorphic expressed sequence tags-simple sequence repeat (EST-SSR) markers, with little or no polymerase chain reaction (PCR) stutter bands, including 21 screened from those obtained previously and 17 newly developed markers, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…However, for some SSR markers, accurate size identification and allele designation can be difficult due to the presence of stutter bands, or stutter peaks. This problem was encountered in our preliminary study in peach as well as extensively reported in other plants (Caruso et al, 2008;Goulão and Oliveira, 2001;Huang et al, 2000;Jones et al, 1997;Song et al, 2002;Teulat et al, 2000;Wang et al, 2016;W€ unsch and Hormaza, 2002). The stutter bands occur as a result of enzyme slippage during amplification and was most common for SSR markers with dinucleotide motifs and the problem is amplified as the repeat number of the alleles increases (Guichoux et al, 2011;Hite et al, 1996).…”
supporting
confidence: 60%
“…However, for some SSR markers, accurate size identification and allele designation can be difficult due to the presence of stutter bands, or stutter peaks. This problem was encountered in our preliminary study in peach as well as extensively reported in other plants (Caruso et al, 2008;Goulão and Oliveira, 2001;Huang et al, 2000;Jones et al, 1997;Song et al, 2002;Teulat et al, 2000;Wang et al, 2016;W€ unsch and Hormaza, 2002). The stutter bands occur as a result of enzyme slippage during amplification and was most common for SSR markers with dinucleotide motifs and the problem is amplified as the repeat number of the alleles increases (Guichoux et al, 2011;Hite et al, 1996).…”
supporting
confidence: 60%
“…Red bayberry has been domesticated by humans for more than 2000a, and thus it is difficult to infer the founder wild populations of the modern red bayberry cultivars. Previous clustering analysis of M. rubra accessions using data of AFLP (Zhang et al, 2009) and SSRs (Jia et al, 2014;Jia et al, 2015;Wang et al, 2016) yielded significantly inconsistent results, with clustered groups ranging from 2 to 6 groups. Although large groups were not well supported by all studies for supporting rates were either very low (< 50%) (Jia et al, 2014;Jia et al, 2015) or not provided (Zhang et al, 2009;Wang et al, 2016), several small groups were nevertheless well supported by SSR based clustering.…”
Section: Discussionmentioning
confidence: 97%
“…Research on the population structure of wild red bayberry in Guangxi province identified two main groups (He et al, 2010). More studies on the genetic diversity and putative clusters of red bayberry accessions yielded quite different results (Zhang et al, 2009;Jia et al, 2014;Jia et al, 2015;Wang et al, 2016). Moreover, the large clusters identified in these studies either had low (< 50%) bootstrap support or had no support rate given.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation